Major achievements are still ahead - Astakhova , V. (New Collegium, 2021)
The article is devoted to the 30th anniversary of Kharkiv University of Humanities “People’s Ukrainian Academy”, a new type of educational institution that has succeeded in implementing the concept of an educational and scientific complex of continuing education. The main stages of this complex process have been identified; the PUA’s achievements as well as the problems and difficulties that its team had to overcome especially at the first stage of the institution’s activity between 1991 and 2006, when experimental work to implement important theoretical developments was underway have been analyzed. Arguments confirming the viability of and prospects for the development of continuing education have been presented.